2022
DOI: 10.4236/jbm.2022.1011016
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity and Phenolic Compounds Content of Extracts from </>Ceratotheca sesamoides</i> Endl and <i>Striga hermonthica</i> (Delille) Benth Used as Antheminthic in Burkina Faso

Abstract: The revaluation of medicinal plants in the veterinary pharmacopoeia is essential for the development of livestock in Burkina Faso. In order to justify the use of C. sesamoides and S. hermonthica in the treatment of gastrointestinal parasitosis of small ruminants, a quantification of phenolic compounds as well as antioxidant activity and acute toxicité evaluation of both plants were performed. Acute toxicity was evaluated by administering a single dose of 2000 mg/kg body weight of aqueous extract of both plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…It is reported that no phytochemical studies have been previously done on plant material and extract; however, the plant material is highly beneficial against several diseases and infections [26,27]. This weed is also reported as an antioxidant due to the presence of numerous properties of phenolic compounds including tannins anthocyanins, apigenin and luteolin [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that no phytochemical studies have been previously done on plant material and extract; however, the plant material is highly beneficial against several diseases and infections [26,27]. This weed is also reported as an antioxidant due to the presence of numerous properties of phenolic compounds including tannins anthocyanins, apigenin and luteolin [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%